2005
DOI: 10.4049/jimmunol.174.9.5444
|View full text |Cite
|
Sign up to set email alerts
|

A Role for CD103 in the Retention of CD4+CD25+ Treg and Control of Leishmania major Infection

Abstract: Endogenous regulatory T cells (Treg) play a central role in the control of excessive or misdirected immune responses against self or foreign Ags. To date, virtually no data are available on the nature of the molecules and signals involved in the trafficking and retention of Treg in tissues where regulation is required. Here, we show that expression of αEβ7 integrin is necessary for the homing of Treg at site of Leishmania major infection. The vast majority of Treg present in the dermis at steady-state conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
256
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 294 publications
(277 citation statements)
references
References 59 publications
(74 reference statements)
16
256
1
4
Order By: Relevance
“…Indeed, yeast cells were found in all biopsies studied (data not shown). In agreement with our findings, the CD4 ϩ CD25 ϩ T cells in L. majorinduced skin lesion (18,23,34,35), S. mansoni egg-induced granulomas (44), and Candida albicans (45) control effector immune response, allowing pathogen persistence. Thus, the enhanced expression and function of cells with a natural Treg phenotype in lesions of patients with PCM suggest this cell type to be a major contributor to parasite persistent and induction of chronicity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, yeast cells were found in all biopsies studied (data not shown). In agreement with our findings, the CD4 ϩ CD25 ϩ T cells in L. majorinduced skin lesion (18,23,34,35), S. mansoni egg-induced granulomas (44), and Candida albicans (45) control effector immune response, allowing pathogen persistence. Thus, the enhanced expression and function of cells with a natural Treg phenotype in lesions of patients with PCM suggest this cell type to be a major contributor to parasite persistent and induction of chronicity.…”
Section: Discussionsupporting
confidence: 77%
“…We found that CD4 ϩ CD25 ϩ T cells expressing CTLA-4, GITR, CD45RO, LAP, and Foxp3 were present in P. brasiliensis-induced lesions. Aside from these markers, the majority of CD4 ϩ CD25 ϩ T cells also expressed CD103, CCR4, and CCR5, all of which are involved in Treg cell migration (24,25,(35)(36)(37). Therefore, the increased presence of CCL17, CCL22 (CCR4 ligands), and the CCL5 (CCR5 ligand) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CD103 has been shown to be necessary for the retention of Tregs at inflamed sites of Leishmania major infection (22). In contrast, recent studies have shown that lack of CD103 has no effect on the absolute number of Tregs in the intestine in murine models of colitis and Trichuris infection (23).…”
Section: Discussionmentioning
confidence: 90%
“…8). It has recently been published that CD103 controls the retention of Treg in leishmania infection of the skin [28]. Knockout mice lacking the CD103 molecule showed no Treg activity during leishmania infection, underscoring the importance of CD103 for Treg functions.…”
Section: Discussionmentioning
confidence: 99%